2020
DOI: 10.1016/s2665-9913(20)30099-0
|View full text |Cite
|
Sign up to set email alerts
|

Stratified care versus usual care for management of patients presenting with sciatica in primary care (SCOPiC): a randomised controlled trial

Abstract: Background Sciatica has a substantial impact on individuals and society. Stratified care has been shown to lead to better outcomes among patients with non-specific low back pain, but it has not been tested for sciatica. We aimed to investigate the clinical and cost-effectiveness of stratified care versus non-stratified usual care for patients presenting with sciatica in primary care. MethodsWe did a two-parallel arm, pragmatic, randomised controlled trial across three centres in the UK (North Staffordshire, No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Patients in the stratified care arm of the trial showed a small but not statistically significant difference in time to first resolution of symptoms (those managed using stratified care reached resolution 2 weeks earlier than those in non-stratified care; a median of 10 weeks versus 12 weeks) [10]. Similarly, exploratory, pre-specified subgroup analysis showed a small difference of 1 week (median) in time to resolution of symptoms, in favour of stratified care for the 'fast-track' patient group.…”
Section: Contribution Of Findings In Providing Insights On the 'Fasttmentioning
confidence: 92%
See 3 more Smart Citations
“…Patients in the stratified care arm of the trial showed a small but not statistically significant difference in time to first resolution of symptoms (those managed using stratified care reached resolution 2 weeks earlier than those in non-stratified care; a median of 10 weeks versus 12 weeks) [10]. Similarly, exploratory, pre-specified subgroup analysis showed a small difference of 1 week (median) in time to resolution of symptoms, in favour of stratified care for the 'fast-track' patient group.…”
Section: Contribution Of Findings In Providing Insights On the 'Fasttmentioning
confidence: 92%
“…As a result, the UK Spinal Taskforce [11] identified the need for evidence on the clinical and cost effectiveness of early referral of patients with severe symptoms for consideration of treatments such as surgery or spinal epidural injections, to assess whether 'fast-tracking' a group of patients can lead to improvement in these patients' outcomes. See [10] full details of the trial procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a trial by Magel et al (2017) found no significant differences in pain reduction between stratified care and usual group for patients in the mediumand high-risk groups at 1-year follow-up. Furthermore, a recent study by Konstantinou et al (2020) found that the use of stratified care for patients with sciatica in primary care was not better than usual care for either clinical or economic outcomes. In 2020, a pilot and feasibility study by Hill et al (2020) investigated the stratified versus non-stratified care for MSK pain, including back, neck, shoulder, knee or multi-site, in primary care using the Keele STarT Musculoskeletal Tool.…”
mentioning
confidence: 98%